2007
DOI: 10.1021/cb700019r
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inositol Phospholipid Headgroup Surrogate Crystallized in the Pleckstrin Homology Domain of Protein Kinase Bα

Abstract: Protein kinase B (PKB/Akt) plays a key role in cell signaling. The PH domain of PKB binds phosphatidylinositol 3,4,5-trisphosphate translocating PKB to the plasma membrane for activation by 3-phosphoinositide-dependent protein kinase 1. The crystal structure of the headgroup inositol 1,3,4,5-tetrakisphosphate Ins(1,3,4,5)P 4 -PKB complex facilitates in silico ligand design. The novel achiral analogue benzene 1,2,3,4-tetrakisphosphate (Bz(1,2,3,4)P 4 ) possesses phosphate regiochemistry different from that of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 33 publications
0
33
0
2
Order By: Relevance
“…Indeed we reported that inositol 1,3,4,5,6-pentakisphosphate (InsP 5 ) specifically blocks Akt activation and possesses pro-apoptotic (Razzini et al, 2000;Piccolo et al, 2004), anti-angiogenic and anti-tumour activity in vivo (Maffucci et al, 2005). In addition, some of us recently demonstrated the targeting of the Akt PH domain with an unusual inositol polyphosphate mimic (Mills et al, 2007). Other phosphatidylinositol-based Akt inhibitors also act by inhibiting Akt targeting to the plasma membrane, including ether lipid analogues and PH domain-targeting inhibitors (Kozikowski et al, 2003;Gills et al, 2006;Crowell et al, 2007) such as perifosine, the most developed Akt inhibitor currently available (Kondapaka et al, 2003).…”
mentioning
confidence: 99%
“…Indeed we reported that inositol 1,3,4,5,6-pentakisphosphate (InsP 5 ) specifically blocks Akt activation and possesses pro-apoptotic (Razzini et al, 2000;Piccolo et al, 2004), anti-angiogenic and anti-tumour activity in vivo (Maffucci et al, 2005). In addition, some of us recently demonstrated the targeting of the Akt PH domain with an unusual inositol polyphosphate mimic (Mills et al, 2007). Other phosphatidylinositol-based Akt inhibitors also act by inhibiting Akt targeting to the plasma membrane, including ether lipid analogues and PH domain-targeting inhibitors (Kozikowski et al, 2003;Gills et al, 2006;Crowell et al, 2007) such as perifosine, the most developed Akt inhibitor currently available (Kondapaka et al, 2003).…”
mentioning
confidence: 99%
“…Benzene 1,2,3,4-tetraA C H T U N G T R E N N U N G kis-A C H T U N G T R E N N U N G phosphate (3) [13] and biphenyl 2,3',4,5',6-pentakisphosphate (4) [14] have been used in other studies and were synthesised by published procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Benzene 1,2-bisphosphate (7), benzene 1,2,3-trisphosphate (10) and benzene 1,3,5-trisphosphate (13) were synthesised by phosphitylation of the appropriate polyphenols with diethyl chlorophosphite to give the corresponding bis-or trisphosphites (Scheme 1). The intermediates were oxidised with mchloroperoxybenzoic acid (mCPBA) to afford the corresponding polyphosphorylated derivatives (6, 9 and 12) in approximately 50 % yield for each compound.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations